EVALUASI TERAPI NON-FARMAKOLOGI PENYAKIT BATUK DAN PILEK DI KELURAHAN KEMANISAN, CURUG, KOTA SERANG - Nur Shobah, Afifah; Noviyanto, Fajrin; Fathiyati, Fathiyati; Fairuza, Filda; Mardianti, Lina; Halimatusyadiah, Leni; Rizqi, Syifa Maulidia; Saefurrohman, Zulius Aditia; Renata, Deo (Jurnal Abdimas Bina Bangsa, 2024)
Community service on "Evaluation of Non-Pharmacological Therapy for Coughs and Cold in Kemanisan Village, Curug, Serang City" was carried out to determine the community's understanding of the causes, prevention and non-pharmacological therapy to treat coughs and colds. The methods used include counseling, distribution of leaflets, masks and hand sanitizer as well as question and answer sessions. Based on the questionnaire, 87% use traditional medicine when they cough and have a kerokan/kerikan, 86% do it, 72% use a mask and 81% hydrate the body. This activity is important to increase awareness of clean and healthy living in treating coughs and cold